Finite Element Modeling of Axially Loaded CFRP-Confined Rectangular Reinforced Concrete Columns - Akbarpour, Hamed; Akbarpour, Masoumeh (Salehan Institute of Higher Education, 2016)
This paper investigates numerically the behaviour of rectangular RC columns strengthened with carbon fiber reinforced polymer (CFRP) composites under uniaxial loading. For this a reason, a parametric study is conducted and the effects of CFRP layers number, compressive strength of unconfined concrete, and fiber orientation on the behaviour of such columns have been studied. The number of CFRP layers has been changed from one to five layers while the fibers are oriented transversely. Compressive strength of unconfined concrete has been increased from 26 MPa to 45 MPa. In addition, three different fiber orientations are considered. The results show that an increase in the number of CFRP layers would enhance the ultimate strength of specimens. Although increasing the number of layers would not increase the ultimate strength of specimens exponentially, but the rate of strength gain would also decrease. Moreover, it is shown that lateral strains increase as the layer number increases. The effect of unconfined concrete strength on the ultimate strength is less for low strength concrete than high strength concrete. Evaluating the effect of fiber orientation shows that the maximum ultimate strength is obtained from transverse orientation and as the angle of orientation increases, the ultimate strength decreases.